Artificial diets and their effects on biological performance of green lacewing, Chrysoperla nipponensis (Okamoto) (Neuroptera: Chrysopidae) - Ahmed, Shafique (2016)
Green lacewings (Neuroptera: Chrysopidae) are the most effective and generalist predators of many soft bodied insects. Chrysoperla nipponensis-B (Okamoto) is a recently recorded lacewing in Malaysia and detailed studies on its biological performance are lacking. Moreover, no comparative research has been done on the mass rearing of C. nipponensis under laboratory conditions on natural and artificial diets and their effect on its biological performance. Therefore, this study was conducted to evaluate the effects of two types of semi-solid artificial diets and two natural diets i.e., Aphis craccivora (Koch) and eggs of Corcyra cephalonica (Stainton) on the growth, development and predation of C. nipponensis larvae and their potential to be used for the mass rearing of C. nipponensis. Composition of artificial diets was same except the addition of whole eggs and ginger in diet-1 and, egg yolk and chemical antimicrobials in diet-2. Results suggested that diet-1 was found to be an alternate to natural diets for the mass rearing of C. nipponensis, as larvae reared on diet-1 performed better in terms of larval duration, fecundity and adult longevity as compared to natural diets. However, survival and weight of larvae and pupae was higher when reared on C. cephalonica eggs. No difference was recorded between diet-1 and C. cephalonica reared larvae in terms of length of 3rd instar larvae, head capsule of 1st and 2nd instar larvae, % adult emergence and their body length. The findings of the life table studies showed that the highest apparent mortality of C. nipponensis (37.26%) was observed in immature stages (1st, 2nd, 3rd and pupae) when reared on C. cephalonica eggs. The sex ratios (proportion of female to male) in the natural and artificial diets were 0.93:1.00 and 0.87:1.00, respectively. The females reared on artificial diet lived one day longer than those reared on C. cephalonica eggs. The maximum life span of females was observed when reared on artificial diet. The maximum oviposition by females reared on C. cephalonica eggs was recorded as 10.4 eggs laid on day five, whereas females reared on artificial diet laid a maximum of 9.26 eggs on day nine. The net reproductive rate (Ro) and maximum gross reproductive rate (GRR) of C. nipponensis fed on C. cephalonica eggs were 69.5 and 223.1 females per female per generation, respectively, while on artificial diet these parameters were 117.24 and 236.89 females per female per generation, respectively. Higher mean generation time (T)and population doubling time of C. nipponensis were 48.16 and 7.00 days observed on artificial diet, respectively. However, intrinsic (r) and finite (λ) rate of increase (females per female per day) of C. nipponensis were higher when reared on C. cephalonica eggs. Studies on the functional response of 3rd instar C. nipponensis larvae reared on artificial diet and C. cephalonica eggs showed a type-II functional response to various densities of aphid (A. craccivora), mealybug (Paracoccus marginatus) (Williams and Granara de Willink) and whitefly (Bemisia tabacci) (Gennadius). Based on Holling‟s disk equation, the highest search rate (á) of larvae (0.68 and 0.40) was observed against mealybug and whitefly when reared on artificial diet and C. cephalonica eggs, respectively. Both, artificial diet and C. cephalonica eggs reared C. nipponensis larvae showed maximum handling time on whiteflies. Chrysoperla nipponensis larvae reared on both diets exhibited maximum predation rate on mealybugs with minimum predation recorded on whiteflies. The same R2 values were recorded for artificial diet and C. cephalonica eggs reared larvae against aphids, mealybugs and whiteflies. The newly recorded green lacewing C. nipponensis is an important predator in Malaysian agro-ecosystems. Chrysoperla nipponensis reared on ginger based artificial diet showed compatible or better performance for various biological and predation parameters, hence can be used for the mass rearing of the predator for the population management of many soft bodied insect pests.